مقارنة الضغوط النفسية بكرة القدم بين طلاب التربية البدنية وعلوم الرياضة في مادة كرة القدم للسنة الدراسية (2022-2023) - فليح, زينب حسن; زبير, ئارى انور; حميد, عماد صدرالدين (Sulaimani Journal for Humanities, 2023)
The research aims to: identify the psychological pressures of football among students of physical education and sports sciences. - Identify the differences that may appear between students of physical education and sports sciences between the four stages in football. As for the purpose of the research, there were statistically significant differences in the level of psychological stress between the four stages of the students of physical education and sports sciences. The research community was selected from the students of the College of Physical Education and Sports Sciences at Al-Mustansiriya University, whose number is (177) male and female students of the second, third and fourth stages of the academic year 2022/2023, (52) students from the four stages of the College of Physical Education and Sports Sciences were excluded. Also (15) students were excluded because of their participation in the exploratory experiment and (22) students to extract the stability of the scale. Thus, the size of the final sample was (140) students with a ratio of (79.09). %). The researchers used the descriptive and comparative method, using the psychological stress scale, which consists of (28) sections. The items of the scale are divided into two groups, the group of positive sections (15), and the group of negative sections (13). The answer is based on five alternatives, after obtaining the results, they were discussed in a scientific manner supported by sources to achieve the objectives of the research, and in light of the results reached by the researchers, the following can be recommended: - Conducting periodic tests to evaluate psychological stress and ways to cope with it among students. - Emphasizing the importance of psychological counseling for university students. - Preparing sufficient supplies for the students in order to reduce the psychological stress they suffer from. - Conducting other studies of the same scale on different samples.